2014
DOI: 10.1007/s00192-014-2473-z
|View full text |Cite
|
Sign up to set email alerts
|

Predicting who will undergo surgery after physiotherapy for female stress urinary incontinence

Abstract: In women with moderate to severe stress incontinence, individual prediction for surgery after initial physiotherapy is possible, thus enabling shared decision making for the choice between initial conservative or invasive management of stress urinary incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
2
6
2
Order By: Relevance
“…Perhaps in the long-term, our outcomes benefit older patients with regard to more successful results. Younger women may be less accepting of incontinence and more likely to report being unsatisfied with the treatment, which corresponds well with the results of Labrie et al, who found that age ≤55 years is a predictor of surgery after physiotherapy [30]. Another explanation may be that older women have more time to perform the PFMT.…”
Section: Discussionsupporting
confidence: 80%
“…Perhaps in the long-term, our outcomes benefit older patients with regard to more successful results. Younger women may be less accepting of incontinence and more likely to report being unsatisfied with the treatment, which corresponds well with the results of Labrie et al, who found that age ≤55 years is a predictor of surgery after physiotherapy [30]. Another explanation may be that older women have more time to perform the PFMT.…”
Section: Discussionsupporting
confidence: 80%
“…The association with younger age is in line with previous findings in women receiving drug treatment or combined treatment for UUI [25]. The association with older age is in line with what Lindh et al found for PFMT via the Internet [10] and with the findings of Labrie et al, with higher rates of crossover to surgery among younger women [26]. The incongruence in these findings is probably due to the different outcomes used, which also depend very much on the expectations of the women, and the non-linear relationship we found between age and improvement.…”
Section: Our Findings In Relation To Previous Datasupporting
confidence: 89%
“…However, this also depends on the outcome used, for example, Lindh et al found that women with higher ICIQ-UI SF scores were more likely to have ≥3 points reduction but less likely to be satisfied with treatment [10]. In line with this, Burgio et al report that women with higher incontinence episode frequency are less likely to be completely dry after behavioral training [12], and Labrie et al report that higher incontinence severity predicts crossover to surgery [26].…”
Section: Our Findings In Relation To Previous Datamentioning
confidence: 98%
“…Conservative treatment (such as pelvic floor exercises) and lifestyle modifications are now recommended as first line treatment for women with SUI and can temporarily or permanently delay surgical management . As a result, patients with a mild first presentation of SUI are likely to be treated nonsurgically initially, and only escalated to MUS once these measures have failed . Recent literature also confirms the increasing role of primary care in the management of early SUI in young women over immediate referral to a specialist gynaecologist, which could also explain the concurrent increase in SUI operations in older age groups, who have failed first line nonsurgical options.…”
Section: Discussionmentioning
confidence: 99%